Measuring the extent of a Social License to Operate: The influence of marine biodiversity offsets in the oil and gas sector in Western Australia. (March 2015) - Richert, Claire; Rogers, Abbie; Burton, Michael
Abstract: Mining companies throughout the world often face a high socio-political risk, in particular because of their impact on the environment. A key indicator of exposure to such risk is a company׳s Social License to Operate (SLO). If a company meets its consumer, shareholders and other stakeholders׳ expectations regarding environmental management, it can gain a SLO. The SLO is an implicit contract between parties which reduces the risk of socio-political challenges to the actions of the company. Here, we apply this concept to a case study of the oil and gas sector in Western Australia, where we evaluate the strength of the SLO granted by the West Australian population to this industry. Our results suggest that, on average, people are not likely to oppose oil and gas projects, because they are economically beneficial for the State. However, it does not achieve as high an evaluation on social legitimacy. We subsequently examine whether the use of marine biodiversity offsets by the oil and gas sector influences SLO. This serves to clarify the social acceptability of offsets as tools to protect the environment. We find that the use of marine biodiversity offsets would improve the SLO of the sector. Highlights: The Social License to Operate is quantified for the oil and gas sector in WA. This is derived for communities who are not geographically close to operations. It is confirmed that 'economic' legitimacy is easier to obtain than higher levels. The use of marine biodiversity offsets does not appear to compromise SLO.